Literary performances of post-religious memory in the Netherlands : Gerard Reve, Jan Wolkers, Maarten 't Hart - Batteau, Jesseka M. (Mobilizing memories, 2022)
"This book offers an in-depth study of iconic literary narratives and images of religious transformation and secularisation in the Netherlands during the 1960s and 1970s. Jesseka Batteau shows how Gerard Reve, Jan Wolkers and Maarten 't Hart texts and performances can be understood as instances of religious and post-religious memory with a broad public impact. They contributed to a widely shared perspective on the Dutch religious past and a collective understanding of what secularisation consists of. This uniquely interdisciplinary approach combines insights from literary studies, memory studies, media studies and religious studies and traces the complex dynamics of the circulation of memory and meaning between literary texts, mass media and embodied performances within a post-religious society"--